Effects of Fertilizer Type on Morphological Characterstics, Forage Yield, Seed Yield and Qualities of Rhodes Grass (Chloris gayana K.) in Northwestern Ethiopia - Anteneh Getie; Bimrew Asmare; Yeshambel Mekuriaw (Scientific Papers Animal Science and Biotechnologies, 2023)
The experiment was conducted to determine the effects of fertilizer types on plant characteristics, forage yield, seed yield and chemical composition of Rhodes grass at Bahir Dar, Ethiopia. The experiment was laid in a randomized complete block design (RCBD). The treatments were: no fertilizer (T1), Bio-slurry compost (T2), NPS fertilizer (T3) and mixture of bio-slurry and NPS (T4) with four replications. Data collected were morphological characteristics such as plant height (PH), number of tillers per plant (NTPP), leaf length per plant (LLPP), leaf to stem ratio (LSR), number of leaves per plant (NLPP), forage dry matter yield and forage qualities harvested at 90 days (50% of blooming stage) except seed yield at three weeks after full flowering stage. Samples of forages were weighed, dried and then ground subsamples taken for analyses of crude protein (CP), ash, dry matter (DM), acid detergent fiber (ADF), neutral detergent fiber (NDF) and acid detergent lignin (ADL). All data were subjected to two way ANOVA procedures of SAS version 9.0. The results showed that the effects of organic and inorganic fertilizer had a significant (p<0.01) effect on all of morphological characteristics were better result with mixing of NPS and bioslurry fertilizer application than other treatments, but a lone of bioslurry and NPS fertilizers also almost similar result but less than in some extent from combined fertilizer treatment. Combining chemical fertilizers with bioslurry gave the highest DM yield (12.63 t/ha) of forage than sole bioslurry (11.8 t/ha) and sole chemical fertilizer (12.03 t/ha). Combined chemical fertilizers with bioslurry gave the highest CP contents (11.25%) of forage than other treatments. In contrast control plot obtained lowest result in all morphological parameters. DMY, seed yield and lowest nutritive value with higher fiber contents. Therefore, the application of combination of bio-slurry and inorganic fertilizer shown the best result in terms of morphological, nutritive value, forage dry matter and seed yield followed by either of fertilizers. Hence, based on the current result, it can be concluded that use of combination of organic and inorganic fertilizer is the best fertilizer as far as Rhodes grass production is concerned in the current study area.